Expiry of an employment relationship for a reason not regulated by law – a gloss to the resolution of the Supreme Court of February 1, 2017, III PZP 11/16 - Drobot, Jolanta (Studia Iuridica Toruniensia, 2020)
The purpose of this study is an attempt to assess the legitimacy of the decision taken by the Supreme Court in the resolution of February 1, 2017, III PZP 11/16. The Supreme Court decided that the employer of employees employed in the Office of the ex-President of the Republic of Poland is the Office, and their employment relationships expire on the day of the death of the ex-President of the Republic of Poland, which is justified by art. 3 in connection with art. 632 § 1 and 2 Labor Code. This view may be controversial in connection with the Court’s recognition of the termination of an employment relationship for a reason not regulated by the law.